Proton Transport in Catalyst Layers of a Polymer Electrolyte Water Electrolyzer: Effect of the Anode Catalyst Loading. Issue 4 (1st January 2019) - Babic, Ugljesa; Nilsson, Elisabeth; Pătru, Alexandra; Schmidt, Thomas J.; Gubler, Lorenz
Abstract : The understanding of loss terms in polymer electrolyte water electrolysis (PEWE) cells is essential to maximize efficiency and minimize cost and enable the technology for energy applications, such as "power-to-X". We adapt the use of the transmission-line model for porous electrodes in conjunction with electrochemical impedance spectroscopy measurements of the cell in the H2 /N2 mode known for fuel cells to PEWE cells to quantify proton transport resistance and double layer capacitance of the anode catalyst layer. Anode catalyst loading was varied between 0.05 and 3.2 mgIrO2 cm −2 . A non-linear relationship was found between the anode IrO2 loading and the proton transport resistance. Catalyst layers with very low IrO2 loading (0.05–0.16 mgIrO2 cm −2 ) had ∼4 times higher mass-specific activity and ∼2 times higher mass-specific capacitance, revealing an inhomogeneous utilization of the catalytic material. The kinetic and transport limitations associated with the anode catalyst layer have been correlated with its morphological features.